TERNATE CITY TOURISM ANALYSIS (CASE STUDY OF JIKOMALAMO BEACH) - Heston, Prince Charles; Kotib, Mohammad (International Journal of Tourism and Hospitality in Asia Pasific, 2022)
The aims of this study are to examine and analyze the effect of a tourist attraction on tourist visits at Jikomalamo beach, to test and analyze the effect of service quality on tourist visits at Jikomalamo beach, and to test and analyze the effect of comfort on tourist visits at Jikomalamo beach, Ternate City. The number of research samples is 30 people. The test tool used is multiple linear regression analysis. The study shows that the tourist attraction variable (X11) t-probability value of 0.290 is greater than the real level of 0.05, so it can be concluded that the variable has a negative and insignificant effect on tourist visits. Moreover, the service quality variable (X2X2) the probability t-value of 0.000 is smaller than the real level of 0.05 so it can be concluded that the service quality variable has a positive and significant effect on tourist visits. The convenience variable (X33) has a probability t-value of 0.003 which is smaller than the significance level of 0.05, so it can be concluded that the comfort variable has a positive and significant effect on tourist visits.Â Keywords: Comfort, Quality of Service, Tourist Attraction, Tourist Visits.Â Â